EFFECT OF SUPPLEMENTATION KAYU MANIS (CINNAMOMUM BURMANNII) EXTRACT IN NEURONAL CELL DEATH PROTECTION IN WISTAR RATS LIR-PSYCHOTIC ON HALOPERIDOL THERAPY - Partan, Radiyati Umi; Hidayat, Rachmat; Saleh, Mgs Irsan; Parisa, Nita; Tamzil, Nia Savitri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to determine the neuronal cell protective effect from kayu manis extract by inhibition activating active caspase-3 in Wistar rats lir psychotic-like behavior on haloperidol therapy. Methods: An experimental in vivo study, an 8-week-old male Wistar rats (n=30) were used. Wistar rats were randomized into six groups. Group A: 5 rats as control without induced psychosis-like behavior and aquadest or drugs. Group B: 5 rats were induced psychosis-like behavior (ketamine 30 mg/kgBW, intraperitoneal for 5 days) and aquadest. Group C: 5 rats were induced psychosis-like behavior and haloperidol 0.5 mg/kgBW, per oral, 28 days. Group D: 5 rats were induced psychosis-like behavior, haloperidol 0.5 mg/kgBW, and kayu manis extract 50 mg/kgBW, per oral, 28 days. Group E: 5 rats were induced psychosis-like behavior, haloperidol 0.5 mg/kgBW, and kayu manis extract 100 mg/kgBW, per oral, 28 days. Group F: 5 rats were induced psychosis-like behavior, haloperidol 0.5 mg/kgBW, and kayu manis extract 200 mg/kgBW, per oral, 28 days. Negative symptoms of schizophrenia were assessed by social interactivity test pre and post. Apoptosis of neuronal cells in ventral tegmental area was assessed by immunohistochemistry of active caspase-3. The area stained was calculated as a percentage of total area within a field by program ImageJ. Results: Active caspase-3 percentage area for group's treatment with only haloperidol was more wide than groups treatment with combination haloperidol and kayu manis extract. Conclusion: Kayu manis extract can protect neuronal cell death through inhibition activating of active caspase-3 in Wistar rats psychotic-like behavior on haloperidol therapy.